A Comparison of Laparoscopies and Laparotomies for Radical Hysterectomy in Stage IA1-IB1 Cervical Cancer Patients: A Single Team With 18 Years of Experience - Qin, Meng; Siyi, Li; Huang, Hui-Fang; Li, Yan; Gu, Yu; Wang, Wei; Shan, Ying; Yin, Jie; Wang, Yong-Xue; Cai, Yan; Chen, Jia-Yu; Jin, Ying; et al. (Frontiers in Oncology, 2020)
Objective: To investigate the safety and efficacy of abdominal radical hysterectomy (ARH) and laparoscopic radical hysterectomy (LRH) in managing early-stage cervical cancer. Methods: This retrospective study comprised patients with FIGO stage IA1 with lymphovascular space invasion (LVSI), IA2, and IB1 cervical cancer who underwent radical hysterectomy performed by a single gynecologic oncology team at Peking Union Medical College Hospital from 2000-2018. The clinicopathological characteristics, surgical outcomes, and survival outcomes were compared between the two groups. Results: The ARH and LRH groups consisted of 84 and 172 patients, respectively. The five-year progression-free survival (PFS) rates were 89.3% and 95.9% in the ARH and LRH groups (P=0.122, adjusted HR=0.449, 95% CI: 0.162-1.239), respectively, while the 5-year overall survival (OS) rates were 95.2% and 98.8%, respectively (P=0.578, adjusted HR=0.650, 95% CI: 0.143-2.961). The presence of more than two comorbidities led to poor OS (P=0.011). For patients with a BMI greater than 24 kg/m2, LRH was associated with better PFS (P=0.039). Compared with ARH, LRH was associated with a shorter operation time (248.8 vs. 176.9 minutes, P<0.001), less blood loss (670.2 vs. 200.9 ml, P<0.001), and lower postoperative ileus rates (2.4% vs. 0%, P=0.042). No significant differences were observed in PFS and OS between 2006-2012，2013-2015, and 2016-2018 in the LRH group (P=0.126 and P=0.583). Conclusion: Compared with ARH, LRH yields similar survival and improved surgical outcomes in patients with early-stage cervical cancer. LRH is not inferior to ARH for select cervical cancer patients treated by a single team with adequate laparoscopy experience.